The Economics and Financing of Urban Schools: Toward a Productive, Solution-Oriented Discourse - Faith E. Crampton (Educational Considerations, 2010)
Across the nation, a surprising number of both critics and advocates of urban schools demonstrate a naïveté about the limits and possibilities of funding in relationship to the academic success of urban students.
Keywords: funding; school districts; urban schools; solution-oriented; discourse; finance; principles; research; discussions